How to evaluate an Internet of Things system: Models, case studies, and real developments. (28th August 2019) - Sicari, Sabrina; Rizzardi, Alessandra; Coen‐Porisini, Alberto
Summary: The paper proposes the use of Node‐RED, a flow‐based programming tool targeted to Internet of Things (IoT), along with a series of case studies related to different IoT contexts, which demonstrate Node‐RED's potentialities and outcomings toward the realization of well‐structured IoT environments. The analyzed applications potentially include a wide range of domains, ranging from smart cities, smart buildings, smart homes/offices, smart retailing, to smart transportation, smart logistics, smart agriculture, smart health, military scenarios, and so on. The motivations behind the presented work are related to the fact that IoT application fields usually involve the same technologies and communication protocols, which are frequently adopted for totally different purposes. Issues such as systems' interoperabiliy, scalability, security and privacy naturally emerge, due to the huge amount of heterogeneous devices acting in the IoT environment itself and to the wireless nature of information transmissions. As a consequence, it is fundamental to dispose of adequate tools for supporting developers in design the network architecture and messages' exchange, in order to realize efficient and effective IoT network infrastructures.